2020
DOI: 10.5296/ijsw.v7i1.16872
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the 2013 Flood on Immigrant Children, Youth, and Families in Alberta, Canada

Abstract: The 2013 flood resulted in devastating impacts for immigrant children, youth, and families in Alberta, Canada. This article presents the findings of the Alberta Resilient Communities (ARC) Project, a collaborative research initiative that aimed to better understand the social, economic, health, cultural, spiritual, and personal factors that contribute to resiliency among children and youth. The study findings indicate that immigrant children and youth resilience is tied to four main themes: 1) Constructive par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…While understanding the risk factors and vulnerabilities of children and youth post-disaster is necessary to address their needs, the need to develop an understanding of the protective factors and strengths they possess is equally pressing as they can serve to mediate resiliency processes following adversity or trauma, such as experiencing a disaster. Research which focuses on protective factors has shown that even in the context of adverse circumstances like disaster, when provided with the proper support systems, children and youth often demonstrate resilience ( 17 , 19 , 28 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While understanding the risk factors and vulnerabilities of children and youth post-disaster is necessary to address their needs, the need to develop an understanding of the protective factors and strengths they possess is equally pressing as they can serve to mediate resiliency processes following adversity or trauma, such as experiencing a disaster. Research which focuses on protective factors has shown that even in the context of adverse circumstances like disaster, when provided with the proper support systems, children and youth often demonstrate resilience ( 17 , 19 , 28 ).…”
Section: Literature Reviewmentioning
confidence: 99%